2003
DOI: 10.1074/jbc.m302097200
|View full text |Cite
|
Sign up to set email alerts
|

A Site of Alcohol Action in the Fourth Membrane-associated Domain of the N-Methyl-D-aspartate Receptor

Abstract: The N-methyl-D-aspartate (NMDA) subtype of ionotropic glutamate receptor is an important mediator of the behavioral effects of ethanol in the central nervous system. Although ethanol is known to inhibit NMDA receptors by influencing ion-channel gating, its molecular site of action and the mechanism underlying this effect have not been established. We have previously identified a conserved methionine residue in the fourth membrane-associated domain of the NMDA receptor NR2A subunit (Met 823 ) that influences de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
94
6

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(107 citation statements)
references
References 33 publications
(25 reference statements)
7
94
6
Order By: Relevance
“…The determinants of ethanol sensitivity and receptor function at each of these positions differ markedly from each other. Recently, we found four pairs of positions at the intersubunit interface in the M3 and M4 domains of the GluN1 and GluN2A subunits, including three positions identified previously (Ronald et al, 2001;Ren et al, 2003bRen et al, , 2007, that interact with each other to regulate both ethanol sensitivity and measures of receptor function such as agonist deactivation and desensitization (Ren et al, 2012). In that study, we identified five positions in the GluN1 and GluN2A subunits that had not been previously shown to regulate ethanol sensitivity.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…The determinants of ethanol sensitivity and receptor function at each of these positions differ markedly from each other. Recently, we found four pairs of positions at the intersubunit interface in the M3 and M4 domains of the GluN1 and GluN2A subunits, including three positions identified previously (Ronald et al, 2001;Ren et al, 2003bRen et al, , 2007, that interact with each other to regulate both ethanol sensitivity and measures of receptor function such as agonist deactivation and desensitization (Ren et al, 2012). In that study, we identified five positions in the GluN1 and GluN2A subunits that had not been previously shown to regulate ethanol sensitivity.…”
Section: Introductionmentioning
confidence: 77%
“…Reports from our laboratory and others have identified a small number of amino acid residues located in the M3 and M4 domains of NMDA receptor GluN1 and GluN2 subunits that influence ethanol sensitivity and channel function (Ronald et al, 2001;Ren et al, 2003bRen et al, , 2007Honse et al, 2004;Smothers and Woodward, 2006;Xu et al, 2012). The determinants of ethanol sensitivity and receptor function at each of these positions differ markedly from each other.…”
Section: Introductionmentioning
confidence: 93%
“…Whole-cell patch-clamp recording was performed as previously described (Ren et al, 2003). Briefly, gigaohm seals were obtained with patch electrodes (series resistance: 2 -10 MΩ, compensation 80%), and cells were voltage-clamped at −50 mV and superfused in extracellular solution containing (in mM): NaCl, 150; KCl, 5; CaCl 2 , 0.2; HEPES, 10; NaHCO 3 , 20; glucose, 10; and sucrose, 10; pH 7.4.…”
Section: Electrophysiological Recordingmentioning
confidence: 99%
“…26). At more physiologically relevant concentrations, alcohols have been shown to induce loss of function of specific proteins, such as ion channels, neurotransmitter receptors, enzymes, and adhesion molecules (27)(28)(29). Structural and biophysical data suggest that binding to the target proteins occurs at discrete sites that are constituted by hydrophobic pockets lined by nonpolar amino acids (26 -29).…”
Section: Discussionmentioning
confidence: 99%